(untitled) (Scientific journal of the Fergana State University, 2024)
The article highlights in detail the issues of environmental education, environmental upbringing, environmental culture, the formation of concepts of environmental competence, environmental safety for future chemistry teachers, the introduction of environmental knowledge into the content of chemistry.